The role of education support in enhancement of entrepreneurial intentions amongst undergraduates in Malaysia / Karen Esther Tan ... [et al.] - Karen, Esther Tan; Ambad, Sylvia @ Nabila Azwa; Nordin, Sakka; Andrew, Jasmine Vivienne; Wong, Nur Syahidah Abdullah (Universiti Teknologi MARA, Perlis, 2021)
Entrepreneurship has long been a topic of interest for many researchers. The economy being volatile has impeded job opportunities for many, particularly amongst youths. In Malaysia specifically, where unemployment has been increasing over the years, measures have been taken by the government to promote entrepreneurship to youth and undergraduates to make them more entrepreneurially inclined. Despite the numerous incentives and programs by the government to encourage youth to be entrepreneurial inclined, the unemployment rate is still high in many countries, particularly Malaysia. This research aims to offer a systematic literature review on the growing role of education support in promoting entrepreneurial intention amongst undergraduates in Malaysia. This research will highlight the increasing importance of education in fostering entrepreneurial intentions amongst undergraduates in Malaysia over the last five years. Through the compilation of past literature and research, this study aims to contribute to entrepreneurship research by discussing the impact of education support as well as highlighting ongoing discussions on education support in nurturing undergraduate entrepreneurial intention.